Ingestion of marine debris by Wedge-tailed Shearwaters (Ardenna pacifica) on Lord Howe Island, Australia during 2005–2018. (August 2018) - Lavers, Jennifer L.; Hutton, Ian; Bond, Alexander L.
Abstract: Annual rates of plastic production have been increasing rapidly since the 1950s. Inadequate or improper disposal of plastic products has contributed to a significant increase in plastic debris in the world's oceans and a corresponding increase in the number of species negatively affected by this debris. Here we investigate trends in the type, amount, and colour of ingested plastic over time, and determine whether ingested plastic contributes to reduced health of Wedge-tailed Shearwaters ( Ardenna pacifica ) on Lord Howe Island, Australia. The results show no clear influence of ingested plastic on body condition, while trends in the prevalence, number, and mass of plastic items ingested per bird during 2005 and 2013–2018 were more variable. There was some evidence adult birds are selecting plastic by colour. Future monitoring of this pan-tropical seabird would provide a unique opportunity to gather data from multiple sites, concurrently. Highlights: No clear influence of ingested plastic on body size (e.g., wing length) Prevalence of ingested plastics was relatively constant over time. The number and mass of ingested plastics was more variable across years. Adult birds may be selecting plastic by colour.